Do Bank Bail-Outs cause Moral Hazard? Evidence from the Subprime Crisis - Florian Hett; Alexander Schmidt (Verein für Socialpolitik, 2010)
In this paper we develop a methodology to test for changes in the strength of market discipline in the corporate bond market. Based on the relationship between equities and bonds of a firm, our method examines the relationship between equity implied information about default probabilities and corporate bond spreads. We interprete a structural change in this relationship as change in market discipline. We then apply this approach to study major events during the current financial crisis, in particular the rescue of Bear Stearns as well as the failure of Lehman Brothers and thereby test popular opinions about the effects of these events. Thereby we rely on the asymmetric effects of bail-outs, as they favor debt holders more than equity holders. We find that the rescue of Bear Stearns led to a significant decline in market discipline. This result is in line with the idea of the bail-out being a signal to market participants that the concept of Too-Big-To-Fail' applies to Investment Banks. Regarding the Lehman case we find that it did re-establish some lost market discipline.
Keywords: G14; G28; H81; 330; bail-out; too-big-to-fail; bond spreads; market discipline; moral hazard